“Abreviación de la exposición de las sentencias de identidad” (Laghu-Vākya-Vṛtti), atribuido a Śaṇkara, con el comentario anónimo “Ofrenda de flores” (Puṣpāñjali) - Hernández Quiroz, Anselmo (El Colegio de México, 2024)
This is the Spanish translation of the text Laghu-Vākya-Vṛtti (Abbreviation of the Exposition of Identity Sentences), attributed to Śaṅkara. It consists of 18 verses that focus exclusively on the exposition of the identity sentence “I am brahman”. The most relevant thing is that together with this text an anonymous commentary self-styled Puṣpāñjali (Offering of Flowers) has come to us, which is also translated into Spanish and that allow us to take a look at the art of Sanskrit interpretation in its post-medieval and pre-modern evolution.